Dampak Motivasi Berprestasi terhadap Kemandirian Belajar Matematika di Sekolah Menengah Pertama - S. Sutama; Eko Wahyudiyanto; Sabar Narimo (Universitas Muhammadiyah Surakarta, 2017)
The purpose of this study was to examine the achievement motivation on mathematicslearning independence. This study is a quasi-experimental study with factorialdesign 2 x 3. The population of class IX students of SMP Negeri 2 Weru Sukoharjo2016/2017 school year and the sampling is done by clusterrandom sampling. Theresearch instrument is a test of mathematics learning independence and achievementmotivation questionnaire. To determine the validity of the instrument test the validityand independence of learning math, using a correlation formula to determine thePoint biserial and reliability using Kuder Richardson formula. While the validity ofthe test achievement motivation questionnaire using the technique of Karl Pearsonproduct moment correlation and reliability testing using the formula used Alpha.Teknik data analysis is the balance test using the Z test, test for normality usingLilliefors, homogeneity test using Bartlett method and hypothesis testing datausing Analysis test variance two streets with different cells. Based on hypothesistesting we concluded that there is achievement motivation on mathematics learningindependence.